2012
DOI: 10.1186/1471-2164-13-62
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and proteomic analyses of the Aspergillus fumigatus hypoxia response using an oxygen-controlled fermenter

Abstract: BackgroundAspergillus fumigatus is a mold responsible for the majority of cases of aspergillosis in humans. To survive in the human body, A. fumigatus must adapt to microenvironments that are often characterized by low nutrient and oxygen availability. Recent research suggests that the ability of A. fumigatus and other pathogenic fungi to adapt to hypoxia contributes to their virulence. However, molecular mechanisms of A. fumigatus hypoxia adaptation are poorly understood. Thus, to better understand how A. fum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
126
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 90 publications
(134 reference statements)
14
126
0
3
Order By: Relevance
“…A comparison with the transcriptome data from the hypoxic response of A. fumigatus cultivated in a batch fermenter at low oxygen levels for 24 h by Barker et al (12) revealed that only 27% of the 867 significantly altered genes were also differentially expressed in our study (see Fig. S2 in the supplemental material).…”
Section: Gene Expression In Long-term Hypoxia-adapted a Fumigatusmentioning
confidence: 55%
See 4 more Smart Citations
“…A comparison with the transcriptome data from the hypoxic response of A. fumigatus cultivated in a batch fermenter at low oxygen levels for 24 h by Barker et al (12) revealed that only 27% of the 867 significantly altered genes were also differentially expressed in our study (see Fig. S2 in the supplemental material).…”
Section: Gene Expression In Long-term Hypoxia-adapted a Fumigatusmentioning
confidence: 55%
“…The role of fermentation during hypoxic growth remains ambiguous, and the electron transport chain (ETC) is still active at low oxygen levels for energy production (11). This was also shown in a previous report on hypoxia-induced changes of the transcriptome and proteome in A. fumigatus over a period of 24 h (here defined as a short-term response) (12). In this work, the authors used a batch cultivation and monitored the A. fumigatus hypoxic response at the time points 2, 6, 12, and 24 h. In a recent proteomic study from our group on the long-term response (5 to 6 days) to hypoxia, A. fumigatus was cultivated in an oxygen-controlled chemostat.…”
mentioning
confidence: 57%
See 3 more Smart Citations